Long-term efficacy of adalimumab in the treatment of uveitis associated with juvenile idiopathic arthritis - Kotaniemi K (Dove Medical Press, 2011)
Kaisu Kotaniemi1,2, Hanna Säilä2, Hannu Kautiainen31Helsinki University Hospital, Helsinki, Finland; 2Orton Orthopaedic Hospital and Rehabilitation Unit, Helsinki, Finland; 3Unit of Primary Health Care, Kuopio University Hospital, Kuopio, FinlandBackground: The purpose of this study was to investigate the long-term effects of adalimumab, a tumor necrosis factor alpha antagonist, in the treatment of uveitis associated with juvenile idiopathic arthritis.Methods: Adalimumab was initiated in 94 patients with juvenile idiopathic arthritis to treat active arthritis and/or active associated uveitis. In 18 patients, therapy was discontinued after a short period because of inefficacy or side effects. The activity of uveitis (using Standardized Uveitis Nomenclature [SUN] criteria and clinical examination) and arthritis (number of swollen or active joints) was evaluated at the start and at end of the study.Results: At the end of the study, uveitis was under good clinical control in two thirds of 54 patients (31% did not need any local treatment and 35% used only 1–2 corticosteroid drops a day), and one third had active uveitis (at least three corticosteroid drops a day). According to SUN criteria, adalimumab treatment for uveitis showed improved activity (a two-fold decrease in uveitis activity) in 28% of patients, with a moderate response in 16 patients, no change in a further 16 patients, and worsening activity (a two-fold increase in uveitis activity) in 13% of patients. The overall proportion of patients with active arthritis decreased. At the beginning of the study, 69% of patients with uveitis had more than two active joints, and at the end of the study only 27% had active joint disease. In 27 patients with juvenile idiopathic arthritis without uveitis on adalimumab, the number of active joints decreased from 93% to 59%. Systemic corticosteroid treatment could be stopped in 22% of patients with uveitis and in 11% of those without uveitis. Most of the patients had received methotrexate, other immunosuppressive therapy, or other biological drugs before initiating adalimumab.Conclusion: Adalimumab is a valuable option in the treatment of uveitis associated with active juvenile idiopathic arthritis.Keywords: adalimumab, juvenile idiopathic arthritis, uveitis